Uses of Proton Pump Inhibitors and Their Prescribing Pattern among the Patients Attending the Out-Patient Department at a Tertiary Care Hospital in Bangladesh (Journal of Enam Medical College, 2020)
Background: Proton pump inhibitors (PPIs) are one of the most frequently prescribed classes of drugs in the world in the treatment of peptic ulcer, dyspepsia and gastro-oesophageal reflux.Objectives: To determine demographic, clinical response and practice characteristics of PPIs among the patients attending the out-patient department of a tertiary care hospital.Materials and Methods: In this prospective observational study 100 patients attending the out-patient department and taking oral proton pump inhibitors (PPI) for different symptoms and duration were included. Patient’s socio-demographic characteristics, PPI-related information (duration, frequency of use, doses and classes of PPIs) and symptomatic responses after taking PPI were noted. Drugs or diseases that influenced the intake of PPI were also recorded. Investigations done before or during PPI use and their findings were also noted.Results: Omeprazole (43%) and esomeprazole (35%) were the most frequently prescribed PPIs. Most of the patients (52%) were on PPI therapy for 1−3 months. Majority of the patients (72%) had taken PPIs on daily basis and 19% patients had taken irregularly or occasionally. Dosing frequency of PPIs prescribed were twice daily in most of the patients (77%). Sixty seven percent (67%) patients had taken PPI prescribed by doctors and 33% patients had taken PPI prescribed by non-doctors. Common indications for prescribing PPIs were heart burn (54%), upper abdominal pain/discomfort (38%) and bloating (33%). Symptoms reappeared after stopping the PPI in most of the patients (40%) and 35% patients had satisfactory relief of symptoms with PPI.Conclusions: Omeprazole and esomeprazole are the most frequently prescribed PPIs. Majority of the patients had taken PPIs on daily basis. In around one-third of the patients PPIs were prescribed by non-doctors. Common indications for prescribing PPIs were heart burn, upper abdominal pain/discomfort and bloating. Symptomatic responses varied after taking PPI and symptoms reappeared after stopping the PPI in most of the patients.J Enam Med Col 2020; 10(1): 10-16